Volcanic climate forcing preceding the inception of the Younger Dryas: Implications for tracing the Laacher See eruption. (15th December 2021) - Abbott, P.M.; Niemeier, U.; Timmreck, C.; Riede, F.; McConnell, J.R.; Severi, M.; Fischer, H.; Svensson, A.; Toohey, M.; Reinig, F.; Sigl, M.
Abstract: Climatic warming from the last glacial maximum to the current interglacial period was punctuated by a ∼1300 years long cold period, commonly referred to as the Younger Dryas (YD). Several hypotheses have been proposed for the mechanism triggering the abrupt inception of the YD, including freshwater forcing, an extra-terrestrial impact, and aerosols from volcanic eruptions. Here, we use synchronised sulphate and sulphur records from both Greenland and Antarctic ice cores to reconstruct volcanic forcing between 13, 200–12, 800 a BPGICC05 (years before 1950 CE on the Greenland Ice Core Chronology 2005; GICC05). This continuous reconstruction of stratospheric sulphur injections highlights a ∼110-year cluster of four major bipolar volcanic signals alongside several smaller events just prior to the YD inception. The cumulative Northern Hemisphere aerosol burden and radiative forcing from this cluster exceeds the most volcanically active periods during the Common Era, which experienced notable multidecadal scale cooling commonly attributed to volcanic effects. The Laacher See eruption (LSE), recently redated to 13, 006 ± 9 cal a BP, falls within our time window of study and has been proposed as a trigger for the YD but a direct volcanic imprint for the LSE in the Greenland ice cores has thus far proved elusive. Comparison of simulated sulphate deposition for mid- and high-sulphur LSE-type emission scenarios to the ice-core estimated sulphate deposition and interhemispheric asymmetry ratios allows several signals between 13, 025 and 12, 975 a BPGICC05 to be proposed as plausible candidates for the LSE. The magnitude and persistence of volcanic forcing directly preceding the YD inception highlights the need to consider stratospheric sulphur injections and their radiative forcing in future analyses and climate model experiments used to explore the mechanisms that triggered this or similar abrupt cooling events. Highlights: Volcanic forcing between 13.2–12.8 ka BPGICC05 reconstructed using ice-core records. Greenland and Antarctic sulphate records and high-precision chronologies utilised. Four bipolar signals in 110 years with radiative forcing exceeding key CE periods. Reconstruction useful for exploring mechanisms that triggered the YD inception. Several volcanic signals identified as candidates for the Laacher See eruption.